Stem-loop-induced ribosome queuing in the uORF2/ATF4 overlap fine-tunes stress-induced human ATF4 translational control - Smirnova, Anna M; Hronová, Vladislava; Mohammad, Mahabub Pasha; Herrmannová, Anna; Gunišová, Stanislava; Petráčková, Denisa; Halada, Petr; Coufal, Štěpán; Świrski, Michał; Rendleman, Justin; Jendruchová, Kristína; Hatzoglou, Maria; et al. (Cell reports, 2024)
Activating transcription factor 4 (ATF4) is a master transcriptional regulator of the integrated stress response, leading cells toward adaptation or death. ATF4's induction under stress was thought to be due to delayed translation reinitiation, where the reinitiation-permissive upstream open reading frame 1 (uORF1) plays a key role. Accumulating evidence challenging this mechanism as the sole source of ATF4 translation control prompted us to investigate additional regulatory routes. We identified a highly conserved stem-loop in the uORF2/ATF4 overlap, immediately preceded by a near-cognate CUG, which introduces another layer of regulation in the form of ribosome queuing. These elements explain how the inhibitory uORF2 can be translated under stress, confirming prior observations but contradicting the original regulatory model. We also identified two highly conserved, potentially modified adenines performing antagonistic roles. Finally, we demonstrated that the canonical ATF4 translation start site is substantially leaky scanned. Thus, ATF4's translational control is more complex than originally described, underpinning its key role in diverse biological processes.
Keywords: sekvence nukleotidů; ribosome; CP: Molecular biology; HEK293 buňky; unfolded protein response; Protein Biosynthesis; proteosyntéza; Activating Transcription Factor 4; translational control; HEK293 Cells; integrated stress response; ribozomy; transkripční faktor ATF4; Stress, Physiological; Ribosomes; translation reinitiation; lidé; otevřené čtecí rámce; Humans; Open Reading Frames; ribosome queuing; Base Sequence; ATF4; fyziologický stres